Experimental Investigation of a Self-Healing Concrete Considering Bacillus Megaterium Bacteri and Fibers : A Review - Singh, Randhir Kumar; Saxena, Ajeet (International Journal of Scientific Research in Civil Engineering, 2021)
It is strong enough to resist compressive load but prone to cracking due to weak in tension which ultimately reduce the life of structure. Hence, any effort to improve the life span of structure will indirectly improve the sustainability of the environment. Cracks in concrete lead to ingress of chemicals in to concrete structure resulting in lower strength and durability In this paper we are presenting review of literatures related to utilization of bacterial effect on concrete.
Keywords: Bacteria; Concrete; Fibers; Strength; Self Healing; Material; Admixtures